2006
DOI: 10.1038/sj.ijo.0803301
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of the BMI for age in paediatrics

Abstract: Must and Anderson,1 in this issue of the journal, have described the basis of body mass index (BMI) for age for the assessment of weight status in children and adolescents. The aims of this short article are to summarise the evidence base on the diagnostic accuracy of BMI, and to expand on what we achieve when defining paediatric obesity on the basis of a high BMI for age. A high BMI for age is not 'obesity' (a high body fat content associated with increased morbidity), per se but a diagnostic test for obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
71
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 22 publications
1
71
0
1
Order By: Relevance
“…A major barrier to nutritional assessment in children is the widespread perception that the assessment methods and definitions of under-and over-nutrition which are currently available lack functional significance and are just 'arbitrary' (1) . We have previously described the development of the lean index and shown that it can discriminate between groups of children with chronic conditions expected to cause differing body compositions (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major barrier to nutritional assessment in children is the widespread perception that the assessment methods and definitions of under-and over-nutrition which are currently available lack functional significance and are just 'arbitrary' (1) . We have previously described the development of the lean index and shown that it can discriminate between groups of children with chronic conditions expected to cause differing body compositions (6) .…”
Section: Discussionmentioning
confidence: 99%
“…There has been a recent resurgence of interest in nutritional assessment of children, driven mainly by the advent of the obesity epidemic (1) but there is also an increasing awareness of its importance in the assessment of underweight, with recognition that a low BMI can reflect a low lean mass rather than low fat stores, which has important implications for nutritional management (2,3) . Assessing body composition robustly is labour intensive and expensive, and is particularly difficult in a field or clinical setting.…”
mentioning
confidence: 99%
“…Systematic reviews have shown that high BMI Z score is a good, perhaps surprisingly good, measure of high fat mass (1), but at lower points in the BMI distribution a very wide range of fat masses exist at the same BMI SD score (Z score) (1,44,45). The use of mean BMI Z score is a poor measure of overweight and obesity in a sample.…”
Section: Measurement Of Exposure and Outcome Variablesmentioning
confidence: 99%
“…O besity continues to increase rapidly across much of the world (1)(2)(3)(4)(5). In England, obesity prevalence defined as body mass index (BMI) Ն95th percentile relative to UK 1990 reference data (4) in 11-15 y olds was 25% in 2004 (5) compared with 17% in 1996 (6) and 5% by definition in 1990 (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation